'Statins in retinal disease'. (May 2018) - Al-Janabi, Ahmed; Lightman, Sue; Tomkins-Netzer, Oren
Abstract Statins are known for their blood cholesterol-lowering effect and are widely used in patients with cardiovascular and metabolic diseases. Research over the past three decades shows that statins have diverse effects on different pathophysiological pathways involved in angiogenesis, inflammation, apoptosis, and anti-oxidation, leading to new therapeutic options. Recently, statins have attracted considerable attention for their immunomodulatory effect. Since immune reactivity has been implicated in a number of retinal diseases, such as uveitis, age-related macular degeneration (AMD) and diabetic retinopathy, there is now a growing body of evidence supporting the beneficial effects of statins in these retinopathies. This review evaluates the relationship between statins and the pathophysiological basis of these diseases, focusing on their potential role in treatment. A PubMed database search and literature review was conducted. Among AMD patients, there is inconsistent evidence regarding protection against development of early AMD or delaying disease progression; though they have been found to reduce the risk of developing choroidal neovascular membranes (CNV). In patients with retinal vein occlusion, there was no evidence to support a therapeutic benefit or a protective role with statins. In patients with diabetic retinopathy, statins demonstrate a reduction in disease progression and improved resolution of diabetic macular oedema (DMO). Among patients with uveitis, statins have a protective effect by reducing the likelihood of uveitis development.